HORIZONTAL COORDINATE ACCURACY OF GOOGLE EARTH ON THE COVERAGE OF SMALL ISLANDS OF MAKASSAR CITY, INDONESIA - Ulfi Syamsiah; Amran, Muhammad Anshar; Nirwana, Ira; Sam, Nurfitri; Muhiddin, Amir Hamzah (Hasanuddin University, 2022)
The presence of high-resolution satellite imagery on Google Earth provides an opportunity for the availability of maps that can be used as a reference for accurate coordinates. Google Earth has been developed to contain high-resolution images, but it warns users about the accuracy of the data regarding the coordinates of the objects covered. Coordinate inaccuracies have the potential to cause problems when used for navigational purposes, or in technical tasks requiring high accuracy such as surveying and mapping applications. Despite these warnings, users are often forced to refer to Google Earth as a reliable data source due to the absence of other data sources. The purpose of this study is to evaluate the accuracy of Google Earth's horizontal coordinates and determine the maximum map scale that can be made based on coordinate data from Google Earth on the coverage of small islands in the Makassar City area. The method used is to compare the object coordinate obtained from Google Earth and the coordinate measured in the field at the same object point. The calculation results show the RMSEH is 2.49 meters and the horizontal accuracy is 4.28 meters. These results indicate that the horizontal coordinates on Google Earth can be referenced to produce a map with a maximum scale of 1: 10,000.